Moral Hazard with Discrete Soft Information1. Issue 287 (27th August 2013) - Roger, Guillaume
<x xml:space="preserve">Abstract</x> I study a model of moral hazard with soft information. The risk‐averse agent takes an action and she alone observes the stochastic outcome; hence the principal faces a problem of ex post adverse selection as well. With limited instruments, the principal cannot solve these two problems independently. To elicit ex post information revelation, he must use an audit mechanism and distort the transfer schedule, as compared to the standard moral hazard problem. This is socially costly in that these transfer distortions imply effort distortions. These results are robust and suggest high‐power contracts may have to be revisited when information is soft.